LAUGHING 'TIL IT HURTS: A CURIOUS CASE OF MIRTH AND MIGRAINE. Issue 10 (9th September 2014) - Shatti, David; Weatherby, Stuart; Pace, Adrian
Abstract : We report the case of a 46 year old woman referred to our Headache Clinic with a 12 month history of severe episodic headache. The headache was left-sided, pressure-like and reliably triggered by outbursts of laughter. Episodes lasted most of the day and were associated with kaleidoscopic visual disturbances, photophobia and nausea. The headache was not triggered by coughing, sneezing, bending forward or neck movement, and could be prevented if she avoided laughing. Her past medical history was significant for asthma and she was on no medication. Neuro-logical examination was normal. MRI of the head and neck did not show any abnormality in the cranio-cervical junction, venous sinuses, cerebral aneurysm or space-occupying lesion. She was interested in herbal remedies and eventually did well on Feverfew and Co-enzyme Q10. Published cases of headache triggered by laughter have generally been associated with type 1 Chiari malformation. Laughter-induced headache may also occur as a primary headache disorder characterised by short-lasting, sharp symptoms. Our patient's associated neurological symptoms suggest her case constitutes a previously unreported form of laughter-induced migraine. We review the published cases of laughter-associated headache and discuss the possible mechanisms of pain in this rare phenomenon.